Thermogenic adipose tissue aging: Mechanisms and implications - Silva, Graciano da Nadyellem; Amato, Angelica Amorim (Frontiers in Cell and Developmental Biology, 2022)
Adipose tissue undergoes significant anatomical and functional changes with aging, leading to an increased risk of metabolic diseases. Senescent adipose tissue is characterized by overall defective adipogenesis, dysfunctional adipokine secretion, inflammation, and impaired ability to produce heat by nonshivering thermogenesis. Thermogenesis in adipose tissue is accomplished by brown and beige adipocytes, which also play a role in regulating energy homeostasis. Brown adipocytes develop prenatally, are found in dedicated depots, and involute in early infancy in humans. In contrast, beige adipocytes arise postnatally in white adipose tissue and persist throughout life, despite being lost with aging. In recent years, there have been significant advances in the understanding of age-related reduction in thermogenic adipocyte mass and function. Mechanisms underlying such changes are beginning to be delineated. They comprise diminished adipose precursor cell pool size and adipogenic potential, mitochondrial dysfunction, decreased sympathetic signaling, and altered paracrine and endocrine signals. This review presents current evidence from animal models and human studies for the mechanisms underlying thermogenic adipocyte loss and discusses potential strategies targeting brown and beige adipocytes to increase health span and longevity.